Cytokine Responses to Stimulation of Whole Blood from Patients with Buruli Ulcer Disease in Ghana - Westenbrink, B. Daan (American Society for Microbiology, 2005)
Buruli ulcer disease (BUD), caused by Mycobacterium ulcerans, follows an indolent course of initial progression to ulceration accompanied by extensive tissue damage. It has been suggested that healing disease stages are accompanied by a protective immune response. We hypothesized that interleukin-4 (IL-4)- or IL-10-induced downregulation of Th-1 responses plays a key role in the progression of early BUD and that healing is accompanied by an augmented Th-1 response. Gamma interferon (IFN-γ), IL-4, and IL-10 responses were measured after in vitro stimulation with phytohemagglutinin (PHA) and tuberculin purified protein derivative (PPD) of whole blood from 39 (23 early- and 16 late-stage) BUD patients and 39 healthy control subjects in Ghana. Additionally, 30 patients with active or treated tuberculosis (TB) serving as PPD-responsive positive controls were studied. Early-stage BUD patients produced significantly lower levels of IFN and IFN-γ/IL-4 ratios compared to late-stage BUD patients after PHA stimulation. Compared to that of controls, IFN-γ production after tuberculin stimulation was significantly higher in late-stage but not in early-stage BUD patients (P = 0.009). IL-10 and IL-4 levels did not differ between BUD patients and controls, although active TB patients had significantly higher IL-10 production levels than did treated TB patients. Multivariate analysis showed no confounding factors. In conclusion, Th-1 down regulation in early BUD appears to reverse in later stages of BUD, although an association with IL-10 or IL-4 production does not emerge from our data. Here we show differences in Th-1-type cytokine production between early- and late-stage BUD that might reflect an improved immune defense over time.